Impacts of drought-tolerant maize varieties on productivity, risk, and resource use: Evidence from Uganda. (November 2019) - Simtowe, Franklin; Amondo, Emily; Marenya, Paswel; Rahut, Dil; Sonder, Kai; Erenstein, Olaf
Highlights: A number of drought - tolerant maize varieties have been developed over the years. The adoption of drought -tolerant varieties is expected to increase productivity improve yield stability, and to reduce the exposure to risk. Drought-tolerant maize varieties also have the potential to empower producers to undertake risky, but high return investments. We apply an endogenous switching regression approach to assess how the adoption of drought tolerant maize varieties in Uganda affects such outcomes. We find that the adoption of drought-tolerant maize varieties increased yield by 15% and reduced the probability of crop failure by 30%. Abstract: Weather variability is an important source of production risk for rainfed agriculture in developing countries. This paper evaluates the impacts of the adoption of drought-tolerant maize varieties on average maize yield, yield stability, risk exposure and resource use in rainfed smallholder maize farming. The study uses cross-sectional farm household-level data, collected from a sample of 840 farm households in Uganda. The adoption of drought-tolerant maize varieties increased yield by 15% and reduced the probability of crop failure by 30%. We further show that the adoption of these varieties increased investments in maize production at the extensive margin through maize area increase and to a more limited extent at the intensive margin through mechanization. The findings show promise for further uptake and scaling of drought-tolerant maize varieties for increased productivity, reduced risk, and the transformation of the maize sector.